Oxidation of L-tryptophan in biology: a comparison between tryptophan 2, 3-dioxygenase and indoleamine 2, 3-dioxygenase. (20th March 2009) - Rafice, Sara A.; Chauhan, Nishma; Efimov, Igor; Basran, Jaswir; Raven, Emma Lloyd
Abstract : The family of haem dioxygenases catalyse the initial oxidative cleavage of L -tryptophan to N -formylkynurenine, which is the first, rate-limiting, step in the L -kynurenine pathway. In the present paper, we discuss and compare structure and function across the family of haem dioxygenases by focusing on TDO (tryptophan 2, 3-dioxygenase) and IDO (indoleamine 2, 3-dioxygenase), including a review of recent structural information for both enzymes. The present paper describes how the recent development of recombinant expression systems has informed our more detailed understanding of the substrate binding, catalytic activity and mechanistic properties of these haem dioxygenases.